INNOVATIVE APPROACHES AND TECHNOLOGICAL ADVANCES IN THE MANAGEMENT OF HYDROCEPHALUS - Jędrzej Sztajura; Małgorzata Gola; Igor Andjelić; Piotr Paździora; Anna Zioła-Paździora; Maciej Wojtacha (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Hydrocephalus is a neurological disorder caused by abnormal accumulation of cerebrospinal fluid (CSF) within the brain ventricles, leading to increased intracranial pressure and neurological impairment. Despite advances in neurosurgery and neuroimaging, optimal management remains a major challenge. This review aims to summarize current therapeutic strategies for hydrocephalus and highlight recent and emerging innovations to improve outcomes and patient quality of life. Materials and Methods: A comprehensive literature search was conducted using PubMed, BioMed Central, Scopus, and Google Scholar. Keywords included: hydrocephalus, NPH, VP shunting, LP shunting, and endoscopic third ventriculostomy (ETV). Reference lists of selected papers were also reviewed. Conclusion: Over the past century, hydrocephalus treatment has progressed from simple drainage to valve-regulated shunts and endoscopic procedures. However, no curative therapy exists, and CSF diversion remains the mainstay. Progress has been incremental due to heterogeneous etiologies, biological complexity, technical constraints, and lack of pharmacological options. Current approaches primarily include ventriculoperitoneal shunting and ETV, selected according to etiology and patient profile. Future directions involve hybrid surgical techniques (ETV with stenting), smart and biocompatible implants, molecular modulation of aquaporins and glial function, gene and stem-cell therapies, and prenatal neuroendoscopic repair demonstrated in experimental models. The next generation of therapy will likely unite mechanical precision with biological insight, shifting from simple drainage toward restoration of CSF physiology and brain health. Integrating surgical, molecular, and etiological perspectives is essential to move beyond symptomatic management.